METHODOLOGY FOR ANALYSING THE ARCHIVES OF THE FRENCH OFFICE FOR REFUGEES AND STATELESS PERSONS ADAPTED TO THE CHILEAN CASE - Jammet-Arias, Nathalie (Revista de Historia Social y de las Mentalidades, 2020)
This article deals with the archival fund of the OFPRA, a French office created in 1952 to rule on asylum applications and replace the administration for administrative management of refugees. The paper describes the background and tries to show how the records can be used to gather valuable information. An analysis method adapted to the study of Chilean exile is proposed with an example of an analysis diagram and the overall results for the specific case of exile roads.
Keywords: Chile; Exil; France; OFPRA; Analysis Methodology